STRATEGI BAGI PERUSAHAAN PERASURANSIAN DALAM MEMATUHI KETENTUAN SINGLE PRESENCE POLICY MENURUT UNDANG-UNDANG NOMOR 40 TAHUN 2014 DAN PERATURAN OJK NOMOR 67/POJK.05/2016 - Glenn Wijaya (Law Review, 2018)
AbstractLaws and regulations in Indonesia on single presence policy created challenges for insurance companies in Indonesia. The single presence policy basically requires insurance companies to only become a controlling shareholder in one insurance company. OJK in this case proposes some methods for insurance companies to fulfill the single presence policy, which are merger, consolidation, acquisition and other corporate actions. Based upon this background, this article then discusses what are the best method to be chosen as well as the procedures of such corporate actions with respect to how insurance companies may obtain OJK approval. This article also discusses upon the recent developments of single presence policy cases.